2011
DOI: 10.1227/neu.0b013e31821ffbb5
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Grading System of Brain and Spinal Cavernomas

Abstract: The proposed grading system showed a convincing correlation with postoperative outcome in surgically treated cavernoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 30 publications
0
30
1
4
Order By: Relevance
“…TJ expression was also not associated with the postoperative outcome grade according to Kivelev. 17 We found no significant association between TJ protein expression and CM multiplicity, CM location, or DVA presence. Most of our cases were classified as Zabramski Type 233 and an association with TJ expression could not be proved.…”
Section: Clinical Relevance Of Tj Protein Expressioncontrasting
confidence: 63%
See 1 more Smart Citation
“…TJ expression was also not associated with the postoperative outcome grade according to Kivelev. 17 We found no significant association between TJ protein expression and CM multiplicity, CM location, or DVA presence. Most of our cases were classified as Zabramski Type 233 and an association with TJ expression could not be proved.…”
Section: Clinical Relevance Of Tj Protein Expressioncontrasting
confidence: 63%
“…The reason for that is probably the independent prognostic impact of the eloquent location, which leads to worse clinical presentation irrespective of the other prognostic variables. No association was also noted with the Kivelev grade of postoperative outcome 17 and the Zabramski type of MRI appearance 3,3 although this could be due to a selection bias as only surgically resected cases were included in the study. Unlike Tu et al, 28 we could not find differences in the occurrence of hemosiderin rings.…”
Section: Discussionmentioning
confidence: 92%
“…16,25,31,48,52,56 These lesions most often occupy the intracranial (mainly supratentorial) compartment. 10,16,25,33,52,66 By contrast, spinal cord cavernous malformations are very rare entities, accounting for 5%-12% of intraspinal vascular malformations. 14,24,29 In comparison with cavernous malformations within the cerebral hemispheres, those involving the spinal cord are thought to result in poorer outcomes.…”
mentioning
confidence: 99%
“…14,24,29 In comparison with cavernous malformations within the cerebral hemispheres, those involving the spinal cord are thought to result in poorer outcomes. 10,33 Historically, cases of intramedullary spinal cord cavernous malformations (ISCCMs) have been infrequently reported and considered exceptionally rare. To the best of our knowledge, Hadlich 26 provided the first published account of an ISCCM in 1903, and 9 years later, Schultze 57 reported the first successful total resection of an ISCCM in a 29-year-old man.…”
mentioning
confidence: 99%
“…We adjusted for known predictors of poor outcome and baseline imbalances, which have also been identified by a recently published surgical grading scale, 23 but the possibility of residual confounding remains. The sample size was modest, but it included all adults newly diagnosed with a CCM in an adult population of 4.3 million over 5 years, making it larger than any other comparative study, 11 and it identified sufficient outcome events over 5 years of follow-up to power a multivariable analysis of the primary outcome (table 2).…”
mentioning
confidence: 99%